Workplace Violence among nursing staff subjective perceptions, preliminary results - Medina-Maldonado, Venus Elizabeth; Pozo, Jenny; Barrera, Janeth; Urgiles, Patricia; Ortiz, Silvana; Yanez, Cristina; Arellano-Verdesoto, Jaqueline; Ruiz, SalomÃ© (Revista Cubana de Enfermería, 2019)
Introduction: Several studies have established the prevalence of workplace violence in the health sector being the nursing staff more likely to experience physical and non-physical violence than other health workers. Objective: Thus, we aimed to research the perceptions of workplace violence in nursing staff in association to type of violence, perpetrators, consequences and protecting measures available in the health institutions. Methods: The study was conducted with a phenomenological method in a major hospital in Quito, Ecuador. N=13/210 professional nurses were selected from a convenience sample and, before starting the discussion, were given information consent forms to sign. The considered selection criteria were being professional, over age 18, and being employers at the hospital as minimum 2 years. The technique selected in data collection was Focus Group Discussion. Results: showed that nursing staff had clarity about what constitutes violence in the workplace such as understanding about the magnitude of the problem, nurses affected by verbal abuse and threats mostly tried to ignore the situation because they considered this to be a typical incident in the workplace, they did not report the situation and it has caused underregistration. The aggressors were mostly staff members, supervisors and relatives of patients. Conclusion: The evidence allowed us to admit that the situation is a significance problem in magnitude and severity. Our recommendations will be oriented toward the implementation of a preventative and minimizing aggression program in the Hospital.